Influenza virus‐mediated suppression of bronchial Chitinase‐3‐like 1 secretion promotes secondary pneumococcal infection. Issue 12 (23rd October 2020) - Karwelat, Diana; Schmeck, Bernd; Ringel, Marc; Benedikter, Birke J.; Hübner, Kathleen; Beinborn, Isabell; Maisner, Andrea; Schulte, Leon N.; Vollmeister, Evelyn
Abstract: Infections of the lung are among the leading causes of death worldwide. Despite the preactivation of innate defense programs during viral infection, secondary bacterial infection substantially elevates morbidity and mortality rates. Particularly problematic are co‐infections with influenza A virus (IAV) and the major bacterial pathogen Streptococcus pneumoniae . However, the molecular processes underlying the severe course of such co‐infections are not fully understood. Previously, the absence of secreted glycoprotein Chitinase‐3‐like 1 (CHI3L1) was shown to increase pneumococcal replication in mice. We therefore hypothesized that an IAV preinfection decreases CHI3L1 levels to promote pneumococcal infection. Indeed, in an air‐liquid interface model of primary human bronchial epithelial cells (hBECs), IAV preinfection interfered with apical but not basolateral CHI3L1 release. Confocal time‐lapse microscopy revealed that the gradual loss of apical CHI3L1 localization during co‐infection with influenza and S. pneumoniae coincided with the disappearance of goblet as well as ciliated cells and increased S. pneumoniae replication. Importantly, extracellular restoration of CHI3L1 levels using recombinant protein significantly reduced bacterial load in influenza preinfected bronchial models. Thus, recombinant CHI3L1 may provide a novel therapeutic means to lower morbidity and mortality associated with post‐influenza pneumococcal infections.